COMPARISON OF MANIFESTATIONS OF GIARDIA AND ASCARIS INFESTATIONS BETWEEN BOTH GENDERS PRESENTING WITH DIARRHEA: comparison of Giardia and Ascaris Infestations among children in GB - Jehanzeb, Kanwal; Haq, Zia Ul; khattak, Saeed Zaman; Shah, Sajid Ali; Lodhi, Munir Akmal; Ashraf, Nadeem (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess the occurrence and intensity of Giardia and Ascaris infestations in children of both genders reporting with diarrhea.Study Design: Comparative cross sectional study.Place and Duration of Study: Paediatrics department, Combined Military Hospital, Gilgit, from Jul 2016 to Jul2018.Methodology: Patients of either gender with worm infestation were included in the study. Patients more than13 years old were excluded. The sampling technique used was non probability consecutive sampling. The stoolexamination (R/E) for the diagnosis of worm infestation was done. Stratification was done with regards to age,mother education, gender, type of water used and post stratification chi square test was applied. p-value was0.613 when calculated for the manifestation between both genders. p-value ≤0.05 was considered significant.Results: Total number of patients in our study was 100. Among them, males were 65 (65%) and females were 35(35%). Mean age of patients in our study was 4.20 ± 2.61 years (Mean ± SD). Abdominal pain being most common symptom in 43 (43%) of patients. Majority of the patients were from 2 to 10 years of age, 79 (79%). Helminthic infestation was the most common observed in 52 (52%) whereas Protozoal infestation was observed in 48 (48%) patients. The most common parasite isolated was Giardia 41 (41%) followed by Ascaris 36 (36%). p-value of 0.613 was found between both gender.Conclusion: In our study Helminthic infestation was more common. The most common parasite isolated wasGiardia followed by Ascaris.